The Diversity of Profiles of the Employees in the Management of Teleworking Conditions: Descriptive Study in the Multiple Banking of Metropolitan Lima During the Year 2021 - Arteaga Torrejón, Mónica (2023)
Diversity management in organizations is positioned as one of the most relevant disciplines according to the context in which they are currently being developed. All this considering that the conditions of the collaborators vary according to their different needs, which must be identified by the companies through diversity management and grouped under shared characteristics to establish conditions that satisfy the collaborators and, together with them, achieve and exceed the objectives that the company establishes. This study presents important findings that provide an approximation to what is established as a new management of working conditions, based on the diversity of the groups that can be found in the same organizations under the new context established from the health emergency in the multiple banking of Metropolitan Lima.